DIABETIC KETOACIDOSIS COMPLICATED BY DEEP VEIN THROMBOSIS IN A NEWLY DIAGNOSED PATIENT WITH TYPE 1 DIABETES MELLITUS WITH UN - Chatchomchuan, Waralee; Thewjitcharoen, Yotsapon; Veerasomboonsin, Veekij; Krittiyawong, Sirinate; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE May-Thurner syndrome is a rare vascular condition where the left common iliac vein is compressed by the right common iliac artery, leading to left iliac vein thrombosis. Here, we present a case of diabetic ketoacidosis (DKA) complicated by deep vein thrombosis (DVT) in a patient with type 1 diabetes mellitus with May-Thurner syndrome. A 41-year-old Thai male with T1D and a recent COVID-19 infection presented with polyuria and significant weight loss. He discontinued insulin treatment for a month and was diagnosed with DKA. Shortly after admission, he developed left lower limb swelling with elevated D-dimer levels. Doppler ultrasound revealed acute DVT in the left common iliac vein with a collateral blood flow, prompting suspicion of extrinsic venous compression including May-Thurner syndrome, later confirmed by CT venography. The follow-up endovascular treatment was planned. In patients with DKA with lower extremity DVT, consider May-Thurner syndrome as a potential cause alongside the known hypercoagulable state.